(Re)penser l’évaluation des apprentissages au postsecondaire en temps de crise : défis à relever et occasions à saisir en période de COVID‑19 - Yerly, Gonzague; Issaieva, Elisabeth (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education, 2021)
During the COVID‑19 pandemic, teachers had a mission: to ensure the pedagogical continuity of teaching, at distance and as an emergency. Thereby teachers had to adapt their assessment practices, both in terms of assessment for learning and assessment of learning. This health crisis has changed the “rules of the game” in terms of assessment, from the technological point of view but also on an emotional and social level. The intention of this article is to provide reflection on assessment for post-secondary teachers facing the challenges and opportunities of such a situation.
Keywords: COVID‑19 pandemic; Pandémie de COVID‑19; assessment; enseignants; post-secondary; postsecondaire; teachers; évaluation des apprentissages